VICTORIAN LITERATURE AND FILM ADAPTATION. Issue 2 (5th May 2017) - Primorac, Antonija
Abstract : "The book was nothing like the film, " complained one of my students about a week or so after the premiere of Tim Burton's Alice in Wonderland (2010 ). Barely able to contain his disgust, he added: "I expected it to be as exciting as the film, but it turned out to be dull – and it appeared to be written for children!" Stunned with the virulence of his reaction, I thought how much his response to the book mirrored – as if through a looking glass – that most common of complaints voiced by many reviewers and overheard in book lovers' discussions of film adaptations: "not as good as the book." Both views reflect the hierarchical approach to adaptations traditionally employed by film studies and literature studies respectively. While adaptations of Victorian literature have been used – with more or less enthusiasm – as teaching aides as long as user-friendly video formats were made widely available, it is only recently that film adaptation started to be considered as an object of academic study in its own right and on an equal footing with works of literature (or, for that matter, films based on original screenplays). Adaptation studies came into its own in early twenty-first century on the heels of valuable work done by scholars such as Brian McFarlane (1996 ), Deborah Cartmell and Imelda Whelehan (1999 ), James Naremore (2000 ), Robert Stam (2000 ), Sarah Cardwell (2002 ), and Kamilla Elliott (2003 ) which paved the way for a consideration of film adaptations beyond the fidelity debate. The field was solidified with the establishment in 2006 of the UK-based Association of Literature on Screen Association (called Association of Adaptation Studies from 2008) and the inception of its journal Adaptation, published by Oxford University Press, in 2008. Interdisciplinary in nature, the field primarily brought together literature and film scholars who insisted that adaptations were more than lamentably unfaithful or vulgar versions of literature mired in popular culture and market issues on the one hand, or merely derivative, impure cinema on the other. The foundational tenets of adaptation studies therefore included a non-judgemental and non-hierarchical approach to the relationship between the text and its adaptation, and a keen awareness of film production contexts. These vividly illustrate the field's move away from discussing fidelity to the "original" which, thanks to the work of Linda Hutcheon (2006 ), started to be increasingly referred to simply as "adapted text." Hutcheon's book came out at the same time as another foundational monograph on the subject, Julie Sanders's Adaptation and Appropriation (2005 ) which contributed to the debate through its focus on intertextual links and the palimpsestuous nature of adaptations, in which debate on fidelity was substituted with the analysis of the distance between the text and its adaptation(s).